Finite Element Analysis of the Nanomechanics of Hard Coatings on a Soft Polymer Substrate by a Spherical Indenter - Chunlai Tian; Pengfei Duan (Advances in Polymer Technology)
Composite has been widely used in various fields due to its advanced performance. To reveal the relation between the mechanical properties of the composite and that of each individual component, finite element analysis (FEA) has usually been adopted. In this study, in order to predict the mechanical properties of hard coating on a soft polymer, the response of this coating system during nanoindentation was modelled. Various models, such as a viscoelastic model and fitting model, were adopted to analyse the indentation response of this coating system. By varying the substrate properties (i.e., Young’s modulus, viscoelasticity, and Poisson’s ratio), Young’s modulus, energy loss, and the viscoelastic model of the coating system were analysed, and how the mechanical properties of the substrate will affect the indentation response of the coating system was discussed.